The Analysis of English Teacher-Made Tests for The Students in SMP Muhammadiyah Palopo - Aliah, Husnani; Asman, Asman; Nasriandi, Nasriandi (Jurnal Serambi Ilmu, 2025)
This study aimed to analyze the quality of English teacher-made tests used in the second semester exam of the 2023/2024 academic year at SMP Muhammadiyah Palopo. The validity, reliability, difficulty level, differentiation index, and distractor strength of the test were analyzed. Data were collected through teacher-made multiple-choice tests as well as student answer sheets. This study used the ANATES program to analyze the test results. The results show that most of the questions were in the very easy category with a percentage of correct answers of more than 85%. Only a few questions have a medium or very difficult level of difficulty. In addition, the differentiating power of most questions was low, indicating the lack of ability of questions to distinguish between students with high and low abilities. Distractors on many questions also proved ineffective in directing students to choose the wrong answer. Overall, these findings indicate the need for improvements to the exam questions, especially in terms of differentiating power and the effectiveness of distractors to improve the overall quality of the test.